Geoarchaeological Investigations of Midden‐Formation Processes in the Early to Late Ceramic Neolithic Levels at Çatalhöyük, Turkey ca. 8550–8370 cal BP. Issue 1 (7th December 2012) - Shillito, Lisa‐Marie; Matthews, Wendy
<x xml:space="preserve">Abstract</x> Anthropogenic midden deposits are remarkably well preserved at the Neolithic settlement of Çatalhöyük and provide significant archaeological information on the types and nature of activities occurring at the site. To decipher their complex stratigraphy and to investigate formation processes, a combination of geoarchaeological techniques was used. Deposits were investigated from the early ceramic to late Neolithic levels, targeting continuous sequences to examine high resolution and broader scale changes in deposition. Thin‐section micromorphology combined with targeted phytolith and geochemical analyses indicates they are composed of a diverse range of ashes and other charred and siliceous plant materials, with inputs of decayed plants and organic matter, fecal waste, and sedimentary aggregates, each with diverse depositional pathways. Activities identified include in situ burning, with a range of different fuel types that may be associated with different activities. The complexity and heterogeneity of the midden deposits, and thus the necessity of employing an integrated microstratigraphic approach is demonstrated, as a prerequisite for cultural and palaeoenvironmental reconstructions.